Quantum chemistry in public higher education institutions in the Brazilian state of Piauí: an analysis of the perceptions of undergraduate chemistry students - de Sousa, Luís Miguel Pinheiro; Cunha, Kariny Mery Araujo; Ferreira, Luciana Nobre de Abreu; de Souza, Alexandre Araujo (Eclética Química, 2024)
Quantum chemistry is a challenging required course in undergraduate chemistry. Despite its unconventional concepts, it is crucial for understanding modern chemistry. This study investigated how students perceive certain topics and the learning process. Interviews were conducted using a Likert scale questionnaire and sixteen content-specific questions. Some responses differed from the existing literature, such as students’ interpretations of the nature of light. In terms of learning, students acknowledged that the topic was complex due to the lack of mathematical foundations and the elevated level of abstraction. Students were primarily seeking the average grade required for admission. The data underscore the need for a deeper discussion of curriculum development and implementation. The curriculum matrix revision could provide space for more substantive thinking about content delivery and assessment processes.